Water-assisted Proton Transfer in Ferredoxin I - Lutz, Stephan (American Society for Biochemistry and Molecular Biology, 2011)
The role of water molecules in assisting proton transfer (PT) is investigated for the proton-pumping protein ferredoxin I (FdI) from Azotobacter vinelandii. It was shown previously that individual water molecules can stabilize between Asp(15) and the buried [3Fe-4S](0) cluster and thus can potentially act as a proton relay in transferring H(+) from the protein to the μ(2) sulfur atom. Here, we generalize molecular mechanics with proton transfer to studying proton transfer reactions in the condensed phase. Both umbrella sampling simulations and electronic structure calculations suggest that the PT Asp(15)-COOH + H(2)O + [3Fe-4S](0) → Asp(15)-COO(−) + H(2)O + [3Fe-4S](0) H(+) is concerted, and no stable intermediate hydronium ion (H(3)O(+)) is expected. The free energy difference of 11.7 kcal/mol for the forward reaction is in good agreement with the experimental value (13.3 kcal/mol). For the reverse reaction (Asp(15)-COO(−) + H(2)O + [3Fe-4S](0)H(+) → Asp(15)-COOH + H(2)O + [3Fe-4S](0)), a larger barrier than for the forward reaction is correctly predicted, but it is quantitatively overestimated (23.1 kcal/mol from simulations versus 14.1 from experiment). Possible reasons for this discrepancy are discussed. Compared with the water-assisted process (ΔE ≈ 10 kcal/mol), water-unassisted proton transfer yields a considerably higher barrier of ΔE ≈ 35 kcal/mol.